Perluasan Ruang Lingkup Kewenangan Pengadilan Agama dalam Penyelesaian Sengketa Ekonomi Syariah di Indonesia - Risyanto, Hamdallah Alfarizky A P; Ambarwati, Mega Dewi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Religious Courts in Indonesia were initially only authorized to examine cases related to marriage, inheritance, wills, grants, waqf, zakat, infaq, shadaqah, and sharia economics as regulated in Law Number 7 of 1989 concerning Religious Courts. Along with the development of sharia economic practices in Indonesia, the scope of the authority of the Religious Courts was expanded through Law Number 3 of 2006 which amended Law Number 7 of 1989. This expansion of authority aims to provide legal certainty, legal protection, and easy access to justice for Muslim communities who transact with sharia principles. However, in practice, the Religious Courts are faced with various challenges, both in terms of human resources, judge competence, and overlapping authority with other judicial institutions. This article aims to analyze the scope of the authority of the Religious Courts in resolving sharia economic disputes, the challenges of implementation in the field, and strategies for strengthening the role of the Religious Courts in the future. The research method used is normative juridical with a statutory approach and case studies. The results of the discussion show that the authority of the Religious Court has a high urgency in supporting the sharia financial ecosystem in Indonesia, although it is necessary to update regulations and increase human resource capacity to realize the principles of simple, fast, and low-cost justice.